ANALYTICAL QUALITY BY DESIGN APPROACH IN RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR THE ESTIMATION OF DUVELISIB - CH, SRUJANI; P, ANNAPURNA; KS, NATARAJ; MANJARI PAWAR A, KRISHNA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: A simple, accurate, and robust RP-HPLC method was developed and validated for the estimation of Duvelisib using analytical quality by design approach. Methods: The critical method parameters (CMP) were systematically optimized using box-Behnken design (BBD). The CMP’s selected were % organic phase composition, column temperature, and flow rate. The critical quality attributes investigated were retention time and theoretical plates. Results: Chromatographic separation was accomplished on Agilent Zorbax Eclipse C18 (150×4.6 mm, 5 μm) column. The optimized and predicted data from Design Expert software consist of mobile phase 0.1 % orthophosphoric acid (46.3%): Acetonitrile (53.7%), pumped at a flow rate of 0.91 ml/min at 32.6°C gave the highest desirability function of 1. The retention time of the drug was found to be 2.85 min. The developed method was validated as per the ICH Q2 (R1) guidelines. Conclusion: Based on the analysis of variance values, the selected models were found to be significant with p<0.05. The results of the validation parameters were within the acceptable limit. The stability of the drug was examined under different stress conditions forcibly and significant degradation was found in acidic condition.